Corrections to the spellings of two tribe names in the leafhopper subfamily Ledrinae (Hemiptera: Cicadellidae) - Jones, Joshua R.; Dmitriev, Dmitry (Zootaxa, 2021)
In 2009, Jones and Deitz published a tribe-level taxonomic revision and reclassification of the cryptic, arboreal leafhopper subfamily Ledrinae Kirschbaum, 1868 (Hemiptera: Cicadellidae), based on cladistic analyses of 235 morphological features for 75 cicadellid species. Their evolutionary reconstructions found strong node support for a monophyletic ingroup comprising five lineages—each morphologically and geographically cohesive—and also identified numerous traditionally placed taxa (sensu Oman et al 1990) that did not belong. In light of the robustness of their results, the authors recognized the five independent ingroup clades as tribes of Ledrinae, and described three of these as new.